Lethal and sublethal effects of cyantraniliprole on Bactrocera dorsalis (Hendel) (Diptera: Tephritidae). Issue 2 (27th May 2014) - Zhang, Ruimin; Jang, Eric B; He, Shiyu; Chen, Jiahua
Abstract BACKGROUND The oriental fruit fly, Bactrocera dorsalis (Hendel), is one of the most globally important insect pests. Studies were conducted with the novel anthranilic diamide insecticide cyantraniliprole to determine its lethal and sublethal effects on B. dorsalis. RESULTS An ingestion toxicity bioassay showed that cyantraniliprole was active against B. dorsalis, and the 72 h feeding LC50 was 3.22 µg g−1 in adult diet for a susceptible strain. Sublethal doses of cyantraniliprole (1.30 µg g−1 adult diet) induced a hormesis effect on B. dorsalis. The mating competitiveness of B. dorsalis treated with cyantraniliprole at 3.27 µg g−1 adult diet was significantly lower when compared with the controls. The lower dose (1.30 µg g−1 adult diet) of cyantraniliprole improved the total mating times of both mating pairs in treated groups and also the mating competitiveness of the treated males when compared with the higher dose and controls. Cyantraniliprole‐treated females of the mated pairs with the lower dose laid more eggs. On the fifth day, female receptivity in the treated group was significantly reduced when compared with the controls. CONCLUSION These results indicate that cyantraniliprole is effective against B. dorsalis. The inhibition and stimulation effect of cyantraniliprole on the adult's mating performance at different concentrations was proved. © 2014 Society of Chemical Industry